Weathering the Global Storm : The Benefits of Monetary Policy Reform in the LA5 Countries. (IMF Working Papers; Working Paper ;, 2010)
This paper highlights that central banks from Brazil, Chile, Colombia, Mexico, and Peru (the LA5 countries) reaped the benefits of what they sowed in successfully weathering the global crisis. The adoption of far-reaching institutional, policy, and operational reforms during the last two decades enabled central banks to build credibility about their commitment with the objective of price stability. Thus, when the 2007 - 08 supply shock and the financial crisis hit the world, the LA5 central banks reacted swiftly and effectively based on a flexible policy framework and with the support of strong macroeconomic and financial foundations. Building on the experience of the LA5 central banks and complementing with recommendations from the IMF's technical advice, the paper provides several suggestions for countries seeking to strengthen the effectiveness of monetary policy.